Telepharmacy in the Digital Age: Improving Accessibility and Efficiency of Pharmaceutical Services (Asian Journal of Pharmaceutics (AJP), 2024)
Telepharmacy, the remote delivery of pharmaceutical services through information and communication technology,enhances access to healthcare, improves patient outcomes, and addresses challenges in underserved areas. Thisreview consolidates evidence from scholarly publications, national health-care documents, and case reports to explorethe global integration and potential of telepharmacies. The COVID-19 pandemic has accelerated telepharmacyadoption, maintaining high-quality pharmaceutical care while adhering to social distancing. Telepharmacy includesservices, such as patient assessment, medication evaluation, prescription verification, and patient education.Countries such as Australia, the US, Canada, and the UK have used telepharmacy for decades, especially in ruralareas. Innovative models such as medication consultation systems, WeChat-based services, and TelepharmacyRobotic Delivery Services improve access to therapies. Studies have shown that telepharmacy has a positiveimpact on disease management, medication adherence, and adverse events. Successful deployment of telepharmacyrequires addressing confidentiality, digital literacy, cultural acceptance, and legal support. Collaborative effortsamong health-care professionals and their integration into the existing systems are essential. As healthcare evolves,telepharmacy is crucial for enhancing clinical safety, expanding pharmaceutical access, and optimizing patient care.